Best Practice Service-Oriented Architecture (SOA): Recommendation and Tips - Astriani, Maria Seraphina (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Companies that have many applications always deal with application integration problems. For the of company necessity, they often yearn for information that an application can be used by other applications. Often a small portion of data from another application is needed in order to complete and support other business functions. They require an architectural approach that can bridge the information between applications. SOA (Service-Oriented Architecture) offers manufacturing services around existing business functions. Applications that wish to communicate with other applications can use the services to achieve business goals. This article will discuss recommendations and tips for implementing SOA best practices in banking.